Temporal trends and rural–urban disparities in cerebrovascular risk factors, in-hospital management and outcomes in ischaemic strokes in China from 2005 to 2015: a nationwide serial cross-sectional survey. Issue 1 (19th August 2022) - Wang, Chun-Juan; Gu, Hong-Qiu; Zhang, Xin-Miao; Jiang, Yong; Li, Hao; Bettger, Janet Prvu; Meng, Xia; Dong, Ke-Hui; Wangqin, Run-Qi; Yang, Xin; Wang, Meng; Liu, Chelsea; et al.
Abstract : Background: Stroke is the leading cause of mortality in China, with limited evidence of in-hospital burden obtained from nationwide surveys. We aimed to monitor and track the temporal trends and rural–urban disparities in cerebrovascular risk factors, management and outcomes from 2005 to 2015. Methods: We used a two-stage random sampling survey to create a nationally representative sample of patients admitted for ischaemic stroke in 2005, 2010 and 2015. We sampled participating hospitals with an economic-geographical region-stratified random-sampling approach first and then obtained patients with a systematic sampling approach. We weighed our survey data to estimate the national-level results and assess changes from 2005 to 2015. Results: We analysed 28 277 ischaemic stroke admissions from 189 participating hospitals. From 2005 to 2015, the estimated national hospital admission rate for ischaemic stroke per 100 000 people increased (from 75.9 to 402.7, Ptrend <0.001), and the prevalence of risk factors, including hypertension, diabetes, dyslipidaemia and current smoking, increased. The composite score of diagnostic tests for stroke aetiology assessment (from 0.22 to 0.36, Ptrend <0.001) and secondary prevention treatments (from 0.46 to 0.70, Ptrend <0.001) were improved. A temporal decrease was found in discharge against medical advice (DAMA) (from 15.2% (95% CI 13.7% to 16.7%) to 8.6% (8.1% to 9.0%); adjusted Ptrend =0.046), and decreases in in-hospital mortality (0.7% in 2015 vs 1.8% in 2005; adjusted OR (aOR) 0.52; 95% CI 0.32 to 0.85) and the composite outcome of in-hospital mortality or DAMA (8.4% in 2015 vs 13.9% in 2005; aOR 0.65; 95% CI 0.47 to 0.89) were observed. Disparities between rural and urban hospitals narrowed; however, disparities persisted in in-hospital management (brain MRI: rural–urban difference from −14.4% to −11.2%; cerebrovascular assessment: from −20.3% to −16.7%; clopidogrel: from −2.1% to −10.3%; anticoagulant for atrial fibrillation: from −10.9% to −8.2%) and in-hospital outcomes (DAMA: from 2.7% to 5.0%; composite outcome of in-hospital mortality or DAMA: from 2.4% to 4.6%). Conclusions: From 2005 to 2015, improvements in hospital admission and in-hospital management for ischaemic stroke in China were found. A temporal improvement in DAMA and improvements in in-hospital mortality and the composite outcome of in-hospital mortality or DAMA were observed. Disparities between rural and urban hospitals generally narrowed but persisted.